Relative Effectiveness of Teachers’ Questioning Strategies in Enhancing Students’ Mathematics Achievement in Gwale Local Government Area of Kano-Nigeria - Ibrahim, Bashir Mohammed (Brillo Journal, 2024)
This study investigated the relative effectiveness of teachers’ questioning strategies in enhancing students’ Mathematics achievement in Gwale Local Government Area of Kano State, Nigeria. The study employed a quasi-experimental design. The population for this study consisted of 8,785 JSS II students. A sample of 135 JSS II students from three intact classes was purposively selected. A simple random sampling technique was used for the study. The instrument used for the pretest and posttest was the Mathematics Achievement Test (MAT), with a reliability coefficient of 0.78 calculated using Pearson’s correlation coefficient (r). The collected data were analyzed using descriptive statistics, such as mean and standard deviation, to answer the research questions, and inferential statistics, including paired sample t-tests and analysis of variance (ANOVA), to test the hypotheses at a 0.05 level of significance. The findings revealed that divergent and convergent questioning strategies had a significant effect on enhancing students’ Mathematics achievement. Additionally, the study found a significant difference between the divergent, convergent, and conventional methods. The researcher recommended that divergent and convergent questioning strategies be included in the Mathematics curriculum for teacher education programs.